More than Cosmetic Changes: The Challenges of Experiments with Police Demilitarization in the 1960s and 1970s. (September 2020) - Schrader, Stuart
In response to civil unrest, many U.S. police forces in the 1960s and 1970s adopted more aggressive postures, including "militarized" uniforms and tactics. A few, however, directed reform efforts toward "demilitarization." This article focuses on the Menlo Park Police Department, in California, led by the maverick reformer Victor Cizanckas. It analyzes his attempts to change relations between the police and the public in his municipality, especially by decreasing incidents of abuse in one predominantly poor, black neighborhood. He instituted, for example, new uniforms and a nonhierarchical bureaucracy in the department. The article details how Cizanckas used emerging networks of law-enforcement professionalization to disseminate his ideas. It also analyzes the failures and challenges of these reform efforts. The article concludes that even radical police reform efforts in the period could not overcome racial inequality or a right-wing backlash against progressive ideas in policing.